Устойчивость пожарной автоцистерны против заноса при торможении - Kulakovskiy, Борис (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The analysis of the published works about the research of the stability of a braking car has been completed. The complex research of the influence of the vertical axis linear moment of the tank with liquid and the ratio of the brake forces of the car on the brake dynamic parameters as well as the tanker stability against a drifting has been carried out. The recommendations to increase the tanker stability to the braking have been proposed.